A Practical Assessment of Field Dependence Independence - Donlon, Thomas F.; Educational Testing Service, Princeton, NJ. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1977)
This report summarizes research and development activity leading to the development of a new test of field-dependence/independence which was carried out with two related projects sponsored by the Graduate Record Examinations Board between September, 1974 and September, 1976. This new test is a group measure, which is machine scorable. In the first project, three versions of a machine scorable group measure, the Figure Location Test (FLT), were developed, using the same set of simple and complex figures. All three versions were administered to a sample of college students, along with the Group Embedded Figures Test and the Portable Rod and Frame Test. All three methods had acceptable levels of reliability and showed evidence of construct validity: however, the Direct-Machine readable version appeared to be most promising, based on analytical data and ease of administration. In a second study the machine readable Figure Location Test was reformulated into two 15-item sections, instead of three 10-item sections. Each of these formats was studied under three different time allowances. On the basis of these two studies, a version with 32 scorable items, organized into two 16-item sections, administrable in approximately 25 minutes, was developed. (Author/MV)
Sponsoring Agency: Graduate Record Examinations Board, Princeton, NJ.
ERIC Note: Paper presented at the Annual Meeting of the New England Educational Research Organization (9th, Manchester/Bedford, New Hampshire, May 4-7, 1977).
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cognitive Style; Cognitive Tests; College Students; Comparative Testing; Correlation; Higher Education; Item Analysis; Measurement Techniques; Statistical Analysis; Test Construction; Test Reliability; Test Validity; Field Dependence Independence -- Figure Location Test (Donlon); Embedded Figures Test -- Rod and Frame Test; Reports, Research